Working for a Living Wage Around the Ivory Tower - Stevens, Andrew (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Since the 1980s, research on employment conditions in post-secondary institutions has focused on the growth of contingent academic workers, or what the Higher Education Quality Council of Ontario (HEQCO) has labelled “non-full-time instructors” (Field, Jones, Stephenson, & Khoyetsyan, 2014). Very little attention, however, has been paid to administrative, physical plant, and other operational staff employed within universities and colleges. Using data from a study of University of Regina students and employees, academic and support staff, this paper confronts the broader conditions of labour around the ivory tower. Employment at a post-secondary institution is analyzed through the lens of living wage research advanced by the Canadian Centre of Policy Alternatives (CCPA) (Ivanova & Klein, 2015). The study reframes the notion of a living wage in a post-secondary institution to include work-life balance, job security, and the realities of dignity and respect in the university workplace.